John Smith - Smith, John, 1580-1631.
Letter written by Smith to the "Wardens and Societtie of the Cordwayners of the Cittie of London" regarding shoes needed by Virginia colonists.
Negative photocopy.
Henry E. Huntington Library, San Marino, Calif.
English explorer and colonial governor of Virginia.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Shoes -- Virginia; Shoemakers -- England -- London; Virginia -- History -- Colonial period, ca. 1600-1775.; Explorers; Governors -- Virginia